2018
DOI: 10.1080/21505594.2018.1551011
|View full text |Cite
|
Sign up to set email alerts
|

Current opinions on autophagy in pathogenicity of fungi

Abstract: The interaction between pathogens and their host plants is a ubiquitous process. Some plant fungal pathogens can form a specific infection structure, such as an appressorium, which is formed by the accumulation of a large amount of glycerin and thereby the creation of an extremely high intracellular turgor pressure, which allows the penetration peg of the appressorium to puncture the leaf cuticle of the host. Previous studies have shown that autophagy energizes the accumulation of pressure by appressoria, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 64 publications
0
72
0
Order By: Relevance
“…Due to the fact that C. neoformans causes infections mainly in immunodeficient individuals [55], affecting up to 223,000 individuals per year [56] and that there is a constraint regarding treatment; it is necessary to broad the knowledge on this fungus biology in order to search for alternatives for treatment and disease control. Understanding the molecular mechanisms that connect both pathogenicity and autophagy could provide us new insights into the relationship established during the fungal infection [57]. One of the central steps of the autophagy pathway is the autophagosome formation in which, in yeast model S. cerevisiae, Atg4 is important to start the autophagosome synthesis by processing Atg8 [58].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that C. neoformans causes infections mainly in immunodeficient individuals [55], affecting up to 223,000 individuals per year [56] and that there is a constraint regarding treatment; it is necessary to broad the knowledge on this fungus biology in order to search for alternatives for treatment and disease control. Understanding the molecular mechanisms that connect both pathogenicity and autophagy could provide us new insights into the relationship established during the fungal infection [57]. One of the central steps of the autophagy pathway is the autophagosome formation in which, in yeast model S. cerevisiae, Atg4 is important to start the autophagosome synthesis by processing Atg8 [58].…”
Section: Discussionmentioning
confidence: 99%
“…Based upon proteomics, is has been suggested that selective ribosome autophagy might occur in Candida orthopsilosis biofilms (Pires et al, 2016), but our study might be the first to directly demonstrate activation of autophagy within a fungal biofilm. In addition, autophagy has been shown to be activated within filamentous fungal plant pathogens as they encounter nutrient poor conditions during the infection process (Kershaw and Talbot, 2009;Zhu et al, 2019) and autophagy is required for fungal plant pathogenesis (Zhu et al, 2019). It will be interesting to investigate what microenvironmental changes might be responsible for activation of autophagy (Corona Velazquez and Jackson, 2018) but, as discussed further below, it is possible that reactive oxygen species (ROS) could be involved.…”
Section: Subcellular Modifications During Biofilm Developmentmentioning
confidence: 99%
“…Autophagy is involved in many important processes, including cell differentiation, development, and responses to nutrient starvation. The disruption of autophagy leads to impaired pathogenesis in some plant fungal pathogens (Sumita et al 2017;Shi et al 2019;Ren et al 2018;Nadal and Gold 2010;Josefsen et al 2012;Deng et al 2009;Liu et al 2016;Zhu et al 2019).…”
Section: Introductionmentioning
confidence: 99%